SPIRITUALITY OF SALUANG SIROMPAK MUSIC IN TAEH BARUAH COMMUNITY, MINANGKABAU - Ikhwan, Nil (E-Journal of Cultural Studies, 2015)
Saluang sirompak is a type of music which has spiritual strength and is performed at Taeh Baruah, Payakumbuh District, Lima Puluh Koto Regency, Minangkabau, West Sumatra. It is performed to bewitch a girl who has humiliated a young man who would like to propose her. This activity is called Basirompak . The Saluang Sirompak performed in Basirompak is supported by what is called gasiang tangkurak , a chant sung with magic formula and an offering. It is performed at one of the seven tanjungs around Taeh Baruah. The problems of the study are formulated as follows. (1) What is the spirituality of the saluang sirompak music performed at Taeh Baruah, Minangkabau like? (2) What is the spiritual function of the saluang sirompak music performed at Taeh Baruah, Minangkabau?, and (3) what is the meaning and implication of the spirituality of the saluang sirompak music on the customs and traditions and religion of the Taeh Baruah community, Minangkabau? The theory of Deconstruction supported by the theory of Aesthetics and the theory of Semiotics was used in the present study. The data were qualitatively analyzed. It was found that the spirituality of the saluang sirompak music caused the people’s mentality and attitude to change. The fact that the activity of Basirompak had never been performed for the last three decades proved this. That indicates that the people living at Taeh Baruah and around it were aware that they should be polite, behave well and have good character, and solve problems, especially the problems related to the friendship between a girl and a young man, amicably.
Keywords: spirituality, saluang sirompak, and basirompak